Leachate Treatment Removal Of Organic Matter Using Ultrasonic-Assisted Electrocoagulation Method - Tahar, Noor Emylia Abdul (Universiti Sains Malaysia, 2022)
This research project aimed to study the removal of organic matter using the ultrasonic-assisted electrocoagulation method. The utilisation of hybrid treatment technologies has been recognised as one of the treatment methods conducted to enhance the efficacy of leachate treatment due to the numerous obstacles, such as the high concentration of pollutants and the limited ability of a single treatment process. EC-US is one of the treatment methods that has been conducted to enhance the efficacy of leachate treatment. The leachate sample was collected from Alor Pongsu Landfill. The factors used in this experiment are voltage (V) and treatment time (minutes). In this study, an ultrasonic-assisted electrocoagulation method was conducted to compare the result with the electrocoagulation method. Additionally, the purpose of this study is to assess the efficiency of both treatments in removing organic matter from landfill leachate in terms of COD and oil and grease. Using the Al-Al electrode, the maximum COD reduction is from EC-US treatment using 9 V, treatment time 10 min with 81.7 %. Meanwhile, for the oil and grease removal, the maximum reduction is 98.1 % during 6 V and 10 min treatment time using the EC-US process.